The Mediation of Rank on the Correlation of Perception and Motivation of Physical Education, Sports and Health Teachers on Interest in Educational Book Publications (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
Educational books as a sub element of scientific publications are rarely sought after in continuing professional development activities by Elementary School Physical Education, Sports and Health Teachers in Sukoharjo Regency in 2021. This study aims to analyze the correlation of perceptions and motivations towards interest in publishing books in the field of education with rank as a variable mediation. This research was conducted in State Elementary Schools in Sukoharjo Regency. The study population was all teachers of Physical Education, Sports and Health totaling 363 teachers. The instrument used in this research is a questionnaire. The method used is descriptive correlation with a quantitative approach without treatment and manipulation of the research sample. Quantitative data collected in the form of numbers. Analysis of the data used is multiple regression analysis and path analysis. The results of research on Elementary School Physical Education, Sports and Health Teachers in Sukoharjo Regency in 2021 stated that there wasn’t significant effect of perception on interest in publishing books in the field of education through rank with a direct influence coefficient value of 0.109 and an indirect influence coefficient value through rank of 0.058 , and there wasn’t significant effect of motivation on interest in publishing books in the field of education through rank with a direct influence coefficient value of 0.215 and an indirect influence coefficient value through rank of 0.141.